Perceptions of universally designed adventure education in high school physical education - Faulds, Nicholas (My University, 2018)
The purpose of this study was to investigate the effects of a universally designed adventure education (UDAE) program on students of varying ability levels. Five data collection techniques were employed to gain a rich understanding of the long term benefits of students with disabilities (SWD) and their nondisabled peers participating in a high school UDAE program. Data collection included semi-structured formal interviews, informal follow up interviews, observations, document analysis, and narrative descriptions. Participants included alumni of a UDAE program, parents of SWD in the program, and faculty members of a school district who initiated or supported the program. Themes developed included Generalization of Teachable Moments; Sense of Community; and Changing Life Perspectives. Findings depicted long-term engagement involving physical activity, special education, adapted physical education, and adventure education/outdoor pursuits amongst multiple populations. In conclusion, participation in UDAE programming during high school physical education can enhance positive feelings between individuals of varying populations that transition into life after graduation.
Keywords: Physical education and training; High schools